Studying the Emotional and Communicative Competence of Students as a Scientific and Pedagogical Problem (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The development of emotional and communicative competence is crucial for the social and emotional development of students. By creating a positive and supportive environment, teachers can help students develop these essential life skills that will prepare them for success in their personal and professional lives. Developing students' emotional and communicative competence is essential as it helps them build healthy interpersonal relationships, regulate their emotions, and express themselves effectively.